2006
DOI: 10.1177/154405910608500210
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Deciduous Upper Lateral Incisor and its Clinical Aspects

Abstract: The upper lateral incisor in humans is often affected by dental anomalies that might be explained developmentally. To address this question, we investigated the origin of the deciduous upper lateral incisor (i2) in normal human embryos at prenatal weeks 6–8. We used serial frontal histological sections and computer-aided 3D reconstructions. At embryonic days 40-42, two thickenings of the dental epithelia in an “end-to-end” orientation were separated by a groove at the former fusion site of the medial nasal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 18 publications
0
69
0
13
Order By: Relevance
“…A similar placode has also been observed in humans: Ooë (1957) reconstructed histological sections of human fetuses and reported that the dental placode of the upper lateral incisor originates from the maxillary process. Recently, more detailed histological 3D reconstruction of human fetuses showed the composite origin of the upper lateral incisor from both the medial nasal and maxillary processes (Hovorakova et al, 2006). These observations explain the dentition in the case of human cleft lip that often affects the upper lateral incisor development.…”
Section: Primary Dental Placode In the Maxillary Process Explains Thementioning
confidence: 89%
“…A similar placode has also been observed in humans: Ooë (1957) reconstructed histological sections of human fetuses and reported that the dental placode of the upper lateral incisor originates from the maxillary process. Recently, more detailed histological 3D reconstruction of human fetuses showed the composite origin of the upper lateral incisor from both the medial nasal and maxillary processes (Hovorakova et al, 2006). These observations explain the dentition in the case of human cleft lip that often affects the upper lateral incisor development.…”
Section: Primary Dental Placode In the Maxillary Process Explains Thementioning
confidence: 89%
“…Именно этим и объясняется большое ко-личество аномалий развития боковых резцов -по дан-ным многих авторов, эти зубы чаще всего подвержены аплазии, микродентии, дупликации, а также в этой обла-сти возникает самое большое число сверхкомплектных зубов и одонтом [12,19,32]. Линия слияния двух очагов одонтогенного эпителия в области боковых резцов видна до восьмой недели внутриутробного развития [12]. Начи-ная с 37-42-го дня гестации, верхняя и нижняя зубные пластинки представляют собой непрерывные подково-образные тяжи.…”
Section: стоматология 2 2016unclassified
“…Верхние боковые резцы представляют собой уникальный случай «слияния» двух центров эпителия и мезенхимы, расположенных на медиальном носовом и верхнечелюст-ных отростках. Именно этим и объясняется большое ко-личество аномалий развития боковых резцов -по дан-ным многих авторов, эти зубы чаще всего подвержены аплазии, микродентии, дупликации, а также в этой обла-сти возникает самое большое число сверхкомплектных зубов и одонтом [12,19,32]. Линия слияния двух очагов одонтогенного эпителия в области боковых резцов видна до восьмой недели внутриутробного развития [12].…”
unclassified
“…Sendo assim, este germe apresenta células da crista neural de duas origens diferentes (Hovorakova et al 2006).…”
Section: Introductionunclassified
“…Entretanto, Hovorakova et al (2006) Se a hipótese deste estudo for positiva o mesmo possibilitará uma melhor adequação para a reabilitação cognitiva e psicossocial dos indivíduos com esses fenótipos.…”
Section: Introductionunclassified